Evaluating Starter Fertilizer Applications in Grain Sorghum Production. Issue 1 (8th April 2019) - Lofton, Josh; Arnall, D. B.; Sharma, Sumit; Nisly, Camron
Abstract : Core Ideas: The application of in‐furrow starter fertilizers did not consistently improve yields over the non‐treated control. Applying high rates of starter fertilizer close to the seed resulted in decreased emergence, which can potentially result in diminished yields. The use of fertilizer additives did not improve yields over non‐treated ammonium polyphosate in‐furrow starter applications. Starter fertilizers have been documented as a successful practice for several crops. However, information on these fertilizer applications on grain sorghum [ Sorghum bicolor (L.) Moench] is very limited. This research was conducted to evaluate the impact of in‐furrow starter fertilizers on grain sorghum establishment and yields in the southern Great Plains. Studies were conducted at four sites across Oklahoma in 2014 and two sites in 2015. Trials evaluated eight in‐furrow starter fertilizer treatments as well as a non‐treated check. Stand counts were collected 1 mo following planting to evaluate impact on stand establishment. At maturity, plot grain weights were used to estimate grain yield. Starter fertilizer applied at high rates (187 L ha −1 ) reduced stands in four of six site locations by an average of 2.0 plants m −2 . This resulted in nearly a 21% decrease in yields. Positive yield effects from in‐furrow starter fertilizers were not consistent, with only one location having significantly greater yields compared with the non‐treated check. The addition of fertilizer additives did not have a significant effect on sorghum yields. However, with the lack of positive yield results from in‐furrow starter fertilizer, it was unexpected that these additives would provide additional yield. These results suggest little yield advantage of in‐furrow starter fertilizers in grain sorghum production. Furthermore, if in‐furrow starter fertilizers are used in sorghum production, higher application rates could result in decreased stand establishment, potentially resulting in lower yields.